NÅR KULTUR SKAL „BEVARES" - perspektiver fra et vestindisk projekt - Olwig, Karen Fog (Tidsskriftet Antropologi, 1996)
Karen Fog Olwig: When culture is to be „preserved“: perspectives from a West Indian research project At the same time as anthropology has begun to apply a more processual perspective to the study of culture as fluid and changing, many of the „fourth world“ peoples studied by anthropologists have become preoccupied with codifying their culture in the form of aboriginal, authentic traditions which can be preserved from change. This concem with cultural traditions is tied to the struggle for human rights by indigenous people. The concept of culture as unchanged traditions is not only in conflict with current anthropological thinking, it is also ill suited to the struggles of peoples who cannot claim this form of ancient indigenous status, but who nevertheless share with „fourth world“ peoples the same need to defend their cultural autonomy. Among this latter group is the people of the Caribbean, who are indigenous to Africa, but came to the islands as part of a process of colonization. This article is based upon a study of the difficulties faced by such a non-indigenous, but nevertheless „native“ community of several centuries standing, in their efforts to defend their cultural and economic autonomy. In the West Indian case modem anthropological theory and the population studied by anthropologists need not be in conflict.